Comparison the Effectiveness of Dialectical Behavior Therapy and Transactional Behavior Analysis on the Cognitive Emotion Regulation of Students with Social Anxiety - Baharlou, Fatemeh; Mahdian, Hossein; Bakhshipour, Abolfazl (Iranian Journal of Educational Sociology, 2022)
Purpose: Students with social anxiety have many problems in the cognitive emotion regulation. As a result, the aim of this study was to comparison the effectiveness of dialectical behavior therapy and transactional behavior analysis on the cognitive emotion regulation of students with social anxiety.Methodology: This research was a semi-experimental with a pre-test, post-test and one-month follow-up design with a control group. The research population was female senior high school with social anxiety in governmental schools of Ashkhane city in the academic years of 2022-2023. In this study, 45 people were selected by purposive sampling method and randomly replaced in three equal groups. Each of the experimental groups was trained in 10 sessions of 90 minute separately and as a group with dialectical behavior therapy and transactional behavior analysis methods, and the control group remained on the waiting list for training. The research tool was Connor et al social anxiety inventory (2000) and Garnefski and Kraaij cognitive emotion regulation questionnaire (1996), and the data obtained from their implementation were analyzed by methods of analysis variance with repeated measure and Bonferroni post hoc test in SPSS version 25 software.Findings: The findings showed that there was a significant difference between the groups in terms of improving cognitive emotion regulation of students with social anxiety, and both methods of dialectical behavior therapy and transactional behavior analysis in compared to the control group significantly improved their cognitive emotion regulation in the post-test and follow-up stages (P0.05).Conclusion: According to the results of this study, therapists, counselors, and psychologists can use dialectical behavior therapy and transactional behavior analysis along with other treatment methods to improve the cognitive emotion regulation of students.